An efficient methodology for fatigue damage assessment of bridge details using modal superposition of stress intensity factors. (December 2015) - Albuquerque, Carlos; Silva, António L.L.; de Jesus, Abílio M.P.; Calçada, Rui
Highlights: A new procedure for the efficient fatigue assessment of bridges is proposed. Modal stress intensity factor concept is employed, enabling modal superposition. Efficiency is enhanced by submodeling techniques. The procedure is applied to the analysis of a complex bridge under real traffic. Fatigue crack propagation simulation is achieved under a short time frame. Abstract: The objective of this paper is to propose an accurate and computationally efficient method for the fatigue assessment of bridge details, using Fracture Mechanics and crack propagation laws. The proposed workflow benefits from the combination of finite element submodeling techniques and modal superposition method with the new concept of modal stress intensity factors. The new methodology was applied to the fatigue analysis of a complex bridge under real traffic conditions. The simulation of fatigue crack propagation in a critical detail of the structure was achieved with minimal computer resources and within a short time frame.